Retrospective tax law: Has Pandora’s Box opened never to be shut again? - Loiacono, Rocco; Mortimer, C. (University of New South Wales, Faculty of Law. Atax, 2017)
The recent Chevron case raised the issue of retrospectivity of legislation. While this issue is not new, it has been argued in the past that there are limits on when governments can resort to enacting retrospective laws. These limits centre on the ability of government to protect the revenue in the public interest. This paper explores the history of retrospective taxation legislation in Australia, and analyses whether such legislation was justified in the circumstances to achieve this goal. The authors argue that the Chevron case not only entrenches the right of governments to enact retrospectively with respect to taxation laws, but unjustifiably extends that right in the name of 'protecting the revenue'. This will have serious implications for taxation practitioners and their clients. The authors contend that retrospective legislation should only be considered in the most egregious circumstances, and that it is incumbent upon governments to acknowledge deficiencies in legislation promptly, and amend such legislation quickly, in order to provide certainty and maintain public confidence in the taxation system.